ASF Shiny app: An interactive web application for exploring premovement active surveillance scenarios for early African Swine Fever detection - Sasidhar Malladi; Peter J. Bonney; Sylvia Wanzala Martin; Amos Ssematimba; Kaitlyn M. St. Charles; Kathleen C. O'Hara; Marta D. Remmenga; Michelle Leonard; Holden C. Hutchinson; Cesar A. Corzo; Marie R. Culhane (SoftwareX)
African Swine Fever (ASF) is a deadly, viral, swine disease with serious socio-economic impacts across the globe. Developing effective active surveillance strategies is critical, given the relatively long herd level incubation period for ASF. We developed an interactive web application that interfaces with a heterogeneous within-herd disease transmission model and enables rapid exploration of various ASF transmission scenarios and premovement surveillance options for finisher swine herds. The application demonstrates the effects of various surveillance design aspects and illustrates the benefit of an enhanced targeted biosecurity interval before movement. Developing such interactive tools can help translate complex mathematical models, and advance communication of ASF risk and surveillance strategies.